The application of natural dyes from rambutan skin for eco-printing on tanned leather - Oetopo, RA. Ataswarin; Despriliani, Ririn; Al Hazmi, Fariz (citeus, 2023)
The use of natural materials is a creative and innovative process to increase the potential of the surrounding environment, such as the use of natural dyes. As rambutan skin has been rarely used and reported as a natural dye, this study explores its usage on leather. In this study, we applied rambutan skin as a natural dye to tanned leather from goat crust skin using the creative eco-printing method. We used an experimental method with a pre-experiment one-shot case study design. Each sample was dyed at different times using distinct solutions during the mordant process. The solution was made from rambutan skin and different solvents, such as alum (AI2(SO4)3), calcium oxide (Ca(OH)2), and ferrous sulfate (FeSO4). The results show that crust-tanned leather from goat skin can be successfully colored with natural dye from rambutan skin. The more amount of dyes used results in a darker color. In addition, the type of mordant used produces a different color. In the eco-printing process, the background color is influenced by the type of mordant used on the blanket, which serves as a cover for the eco-print process. Meanwhile, the leaves stop the mordant from penetrating the leather and become the source of the motive.